Investigation of CO2 adsorption on nitrogen-doped activated carbon based on porous structure and surface acid-base sites - Guo, Tianxiang; Zhang, Yonghe; Chen, Jiahui; Liu, Wenshuo; Geng, Yuhan; Bedane, Alemayehu Hailu; Du, Yarong (Case studies in thermal engineering, 2024)
The purpose of this paper is to reveal the effects of porous structure and surface acid-base sites on CO2 adsorption for those nitrogen-doped activated carbons, which were prepared in a tube furnace with anaerobic conditions (TF) and muffle furnace with oxygen-poor conditions (MF), respectively. Subsequently, the porous structure and surface group distribution of the prepared activated carbons TF and MF were characterized in detail through those methods such as scanning electron microscope (SEM), Brunauer-Emmett-Teller (BET), Barret-Joyner-Halenda method (BJH), Horvath-Kawazoe method (HK), Dubinin-Radushkevich method (DR), mercury intrusion porosimetry (MIP), non-local density functional theory method (NLDFT), (in-situ) Fourier transform infrared spectroscopy (FTIR), Raman spectra (RS), X-ray photoelectron spectroscopy (XPS), and temperature programmed desorption (TPD). Then the thermodynamic and kinetic characteristics of CO2 adsorption such as adsorption capacity, selectivity, and activation energy were systematically investigated based on the static volumetric method and dynamic adsorption method. The results showed that the anaerobic or oxygen-poor preparation atmosphere affected the micropore volume and surface functional group distribution of activated carbons. Thus the activated carbon TF exhibited a higher adsorption capacity of CO2 (7.9 mmol g−1, 100 kPa and 273 K) and longer dynamic breakthrough time due to the higher microporosity (Vmic/Vt = 90 %), while the activated carbon MF exhibited the higher selectivity (14.7, CO2/N2 molar ratio of 1:1) and adsorption rate due to the higher nitrogen and oxygen contents (11.23 %, 13.53 %) in the main forms such as pyrrole nitrogen (N-5), carbony, and carboxyl. Overall, CO2 adsorption on the activated carbons was verified to be a dominant physical adsorption and exothermic process, which was suitable to be described by a quasi-first-order dynamic model. Meanwhile, compared with TF, the activated carbon MF exhibited the higher activation energy of CO2 adsorption (12.98 kJ mol−1 for TF and 17.23 kJ mol−1 for MF), accompanied by the larger rate constants (k1) and diffusion coefficients (D). The higher activation energy for MF meant that the adsorption temperature had a stronger effect on the rate constant during CO2 adsorption.